A perfekcionizmus értelmezése, mérése és iskolai vetületeinek bemutatása - Nagy, Zoltán (Magyar Pedagógia, 2019)
While perfectionism research stems from the field of psychology, its relevance in educational science is not neglectable. Relentlessly striving for unattainable goals can easily leave students mentally and emotionally exhausted, which inevitably leaves its mark on their academic performance, as well as their well-being. Perfectionism itself is most often defined as a trait, which entails that it stays relatively stable through time, and is not context dependent. Since the unidimensional approach of the eighties, it has been linked with anxiety, aggression and interpersonal conflicts, as students whose perfectionistic expectations are directed towards others, accompanied by a sense of entitlement and hypercriticism, can hurt a classroom’s atmosphere and cause unnecessary amount of stress on peers and teachers alike. The present study’s goal is to synthetize the most relevant milestones of perfectionism research from the previous decades, while giving the readers an overview on its most widely-used models and instruments. The study also discusses possible reasons why certain individuals become perfectionistic, and the effect perfectionism has on learning and education. The effects to be delineated are categorized based on the aspect of school life they influence. First, perfectionism’s effect on the academic domain is discussed, including its correlations with academic performance, self-regulated learning and learning strategies, followed by the discussion of perfectionism’s relationship with concepts belonging to the category of affect and cognition, such as impostor-syndrome, counterfactual thinking or burnout.